Emergency Department Nurses\'s Knowledge about Forensic Nursing - Leila Feizi Nazarloo; Mitra Sedghi Sabet; Fateme Jafaraghaee; Ehsan Kazemnezhad Leyli; Morteza Rahbar Taromsari; Avinish Jolly (Guilan University of Medical Sciences, 2017)
Introduction: Forensic nursing makes the relation between medical profession and judicial system using the forensic science in prevention, intervention and treatment guidance. Increasing the nurses knowledge of forensic nursing will provide high quality, safe and holistic nursing. Objective: This study aimed to determine the level of emergency nurses knowledge about forensic nursing. Materials and Methods: This descriptive cross-sectional study was conducted on 195 nurses working in emergency department of educational hospitals in Rasht city by census sampling. Data was gathered by a researcher-made questionnaire. The responses had been scored from 0 to 17. Scores had been categorized as 0-5= poor, 6-11= medium, 12-17= good and in three levels of poor (0-33% of total scores), medium (34-66% of total scores) and good (67-100% of total scores). Data was analyzed using descriptive (means and standard deviation) and Inferencial (statistical tests of Man Whitney, Kruskal-Wallis, Friedman, Logistic Regression) statistics. Significance level was considered less than 0.05. Results: Findings showed that work shifts of 87.2% of subjects were rotated, 89.7% were clinical nurses, with work experience of mean 6.66 years in nursing profession and mean 3.73 years in emergency department. 95.4% of subjects had no education about managing the forensic patients, 92.3% had stated that there was no documented guideline in caring of forensic patients and 95.9% had educational needs for managing the forensic patients. Data showed that only 0.51%, 54.36% and 45.13% of the subjects had good, medium and poor knowledge on forensic nursing, respectively. The most and least level of knowledge was on identification of forensic patient and protection of forensic evidences respectively. There was a significant relationship between knowledge on forensic nursing and sex (P=0.015) and organizational position (P=0.021). Conclusion: In order to provide holistic care to forensic patients, the role of forensic nurses in emergency departments is especially important. Findings emphasis that there is a need to specialized education about forensic nursing in Iran